Reconfigurable Intelligent Surface-Assisted RF Wireless Power Transfer for Internet of Things System: Modeling and Evaluation - Arif Abdul Aziz; Istiqomah; Suratman, Fiky (Buletin Pos dan Telekomunikasi, 2024)
This work studies the utilization of reconfigurable intelligent surfaces (RIS) for assisting radiofrequency (RF)-based wireless power transfer (WPT) in the Internet of Things (IoT) system. The RIS device in this system is utilized to provide the line of sight (LOS) path when an obstacle blocks the direct power transmission from the transmitter to the receiver. This work presents a comprehensive modeling of the RIS-assisted RF WPT for IoT systems, which includes the spatial model, the RIS-assisted RF WPT model, and the total receiver power model. The performance of RIS-assisted RF WPT is evaluated by simulation matched to the IoT system. In all simulation tests, the obstacle is located between the transmission and the receiver, eliminating direct power transfer. By simulation, it has been verified that the RIS device can assist the RF WPT in the IoT system. The receiver can achieve 0,4714% power transfer efficiency at a distance of 1 meter from the RIS device. Meanwhile, 0,0290% power transfer efficiency is achieved within a 15-meter distance from the RIS device. Furthermore, the performance of RIS-assisted RF WPT with various numbers of unit cells in the RF WPT system is investigated. It has been found that increasing the number of unit cells in RF WPT after a certain number is ineffective for the RF WPT in an IoT system